2003
DOI: 10.1002/cne.10851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gustatory nerve transection and regeneration on quinine‐stimulated Fos‐like immunoreactivity in the parabrachial nucleus of the rat

Abstract: The distribution of quinine-stimulated Fos-like immunoreactivity (FLI) in several subdivisions of the parabrachial nucleus (PBN) known to be responsive to gustatory stimulation was examined in rats in which the chorda tympani nerve (CT) and/or glossopharyngeal nerve (GL) was transected (Experiment 1) and in rats in which the GL was transected with regeneration promoted or prevented (Experiment 2). We confirmed previous findings in the literature by demonstrating that rats intraorally infused with 3 mM quinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Neurons in the PBN, the second-order gustatory relay station in the rat central gustatory pathway, are known to induce c-fos expression in response to gustatory and visceral stimuli (16,22,23,31,32). The present study showed that PBN neuronal responses at least at the early phase (15 s) of taste stimulation were not altered after the acute blockage of c-fos mRNA translation (Fos protein synthesis) by AS-ODN within the PBN, and that the same treatment did not affect the expression of LiCl-induced Fos-li-positive cells in the CeA.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the PBN, the second-order gustatory relay station in the rat central gustatory pathway, are known to induce c-fos expression in response to gustatory and visceral stimuli (16,22,23,31,32). The present study showed that PBN neuronal responses at least at the early phase (15 s) of taste stimulation were not altered after the acute blockage of c-fos mRNA translation (Fos protein synthesis) by AS-ODN within the PBN, and that the same treatment did not affect the expression of LiCl-induced Fos-li-positive cells in the CeA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intrinsic signals obtained are mainly the result of stimulation of anterior tongue and palate receptors. However, recent studies showed that, in rats, the neural coding of taste modality depends primarily on the inputs of the facial nerve (anterior tongue and palate), whereas the glossopharyngeal projections (lateroposterior tongue) seem to be more involved in oromotor acceptance/rejection behaviors (King et al, 1999(King et al, , 2003Simon et al, 2006). In addition, all modalities are represented in the anterior part of the oral cavity (Chandrashekar et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the characteristic pattern of Fos-like immunoreactivity (FLI) stimulated by quinine in the rostral nucleus of the solitary tract (NST) (see Refs. 11,38) and in the parabrachial nucleus (PBN) that is disrupted by GL transection returns to normal on regeneration of the nerve (12,13).…”
mentioning
confidence: 98%